Pengaruh Dukungan Sosial Teman Sebaya terhadap Grit pada Mahasiswa Anggota PSM di Universitas “X” Bandung - Naomi Pangaribuan; Jane Savitri (Humanitas (Jurnal Psikologi), 2019)
Based on a study of 95 students member of the PSM in “X” University Bandung found that there is significant peers support effect on grit (R2 = 18,4%, ? = 47,871, and ? = 0,001). The four types of social support also have a significant influence on grit, namely emotional / esteem support (? = 0,632; R2 = 13,8%; ? = 0,000), tangible / instrumental support (? = 0,902; R2 = 9,6%; ? = 0,002), informational support (? = 0,659; R2 = 16,2%; ? = 0,000), and companionship support (? = 1,166; R2 = 12,6 %; ? = 0,000). The researcher suggested that students of PSM members be open to the support given by peers. PSM Management can support activities or programs that support PSM members to remain consistent with their interests and diligence in fulfilling satisfaction in special support for PSM from peers. In addition, further researchers can discuss other factors that can affect grit in addition to social support from peers. Keywords: Grit, emotional support, instrumental support, informational support, companionship support